Attitude aspect in safety practices in workshop among student in Industrial Training Institute - Ngah Deman, Enda Nurwani; Minghat, Asnul Dahar; Mustakim, Siti Salina (Istanbul Kultur University, 2018)
The purpose of this study is to examine the safety practices in the workshop among students at the Industrial Training Institute (ITI) in terms of attitude aspect. A good attitude in safety, while in the workshop parallel to the rules will make the working atmosphere in the workshop safe and free from the risk of accidents. The actual study was conducted and the information was obtained by distributing questionnaires to respondents consisting of 176 students from two industrial training institutes. The data were analyzed using IBM Statistical Package for Social Sciences (SPSS) software version 20. Analysis made is translated into mean, frequency and percentage. Findings show that the student attitudes are very high in safety practices in workshops at the Industrial Training Institute.